STRATEGI MANAJEMEN RISIKO KREDIT DALAM PEMBIAYAAN UMKM DARI BANK SYARIAH : STUDI KASUS BANK SYARIAH INDONESIA KC SURABAYA JEMUR HANDAYANI - Arifin, Vedian Recitra; Milad, Mohammad Khusnu (Growth, 2025)
This study aims to analyze credit risk management strategies in financing Micro, Small, and Medium Enterprises (MSMEs) implemented by Bank Syariah Indonesia (BSI), considering that credit risk is a major challenge in Islamic banking due to the profit-sharing system, which potentially increases the level of non-performing financing (NPF). Using a qualitative approach with a case study method, this research collects data through in-depth interviews with risk managers, credit analysts, and MSME entrepreneurs, as well as document analysis of risk management policies and BSI’s annual reports. Thematic analysis techniques are applied to identify patterns in the risk mitigation strategies implemented. The findings indicate that BSI applies various risk mitigation strategies, such as implementing Sharia-based business feasibility assessments, collaborating with microfinance institutions like Baitul Maal wa Tamwil (BMT), and optimizing monitoring and collection systems. Internal factors, such as the quality of credit risk analysis, and external factors, including global economic conditions and regulatory changes, play a crucial role in determining the effectiveness of these strategies. By understanding the dynamics of credit risk in MSME financing, this study provides valuable insights for stakeholders in the Islamic banking industry to develop more effective risk mitigation policies, enhance MSMEs’ access to financing, optimize bank profitability, and ensure the stability of the Islamic financial sector in Indonesian.